The Determinant Factors Affecting the Employee Performance Improvement of Educational Institution, State Institution and State-owned Enterprise - Ana Sriekaningsih; Mariman Darto; Agus Subekti (STKIP Singkawang, 2018)
This study focuses on the factors that affect the employee performance in terms of institutions where they work. There are three objects or locations that become the research focus, namely educational institutions represented by the state university in East Kalimantan, government institutions represented by the State AdministrationInstitution (LAN) and state-owned institutions represented by PT. Pupuk Kaltim Tbk. The research results show that employee performance is influenced by three factors, namely competence, work motivation, and organizational culture.The performance of government employees is influenced by three factors, namely religiosity, organizational culture, and organizational citizenship behaviors (OCB). And performance of state-owned employees is influenced only by work motivation.